Epigenetic Transgenerational Inheritance of the Effects of Obesogen Exposure - Mohajer, Nicole; Joloya, Erika M.; Seo, Jeongbin; Shioda, Toshi; Blumberg, Bruce (Frontiers in Endocrinology, 2021)
Obesity and metabolic disorders have become a worldwide pandemic affecting millions of people. Although obesity is a multifaceted disease, there is growing evidence supporting the obesogen hypothesis, which proposes that exposure to a subset of endocrine disrupting chemicals (EDCs), known as obesogens, promotes obesity. While these effects can be observed in vitro using cell models, in vivo and human epidemiological studies have strengthened this hypothesis. Evidence from animal models showed that the effects of obesogen exposure can be inherited transgenerationally through at least the F4 generation. Transgenerational effects of EDC exposure predispose future generations to undesirable phenotypic traits and diseases, including obesity and related metabolic disorders. The exact mechanisms through which phenotypic traits are passed from an exposed organism to their offspring, without altering the primary DNA sequence, remain largely unknown. Recent research has provided strong evidence suggesting that a variety of epigenetic mechanisms may be underlie transgenerational inheritance. These include differential DNA methylation, histone methylation, histone retention, the expression and/or deposition of non-coding RNAs and large-scale alterations in chromatin structure and organization. This review highlights the most recent advances in the field of epigenetics with respect to the transgenerational effects of environmental obesogens. Changes in chromatin organization and structure may be the most plausible explanation for how some diseases predispositions are heritable through multiple generations, including generations that were not exposed. A solid understanding of these possible mechanisms is essential to fully understanding how environmental exposure can lead to inherited disease susceptibility.